2019
DOI: 10.3390/app9040646
|View full text |Cite
|
Sign up to set email alerts
|

Lignocellulosic Composites from Acetylated Sunflower Stalks

Abstract: Sunflower stalks could be an alternative raw material for use in the particleboard industry since the requirements of P1 general purpose boards for use in dry conditions and P2 boards for interior fitment for use in dry conditions are easily satisfied. Acetylation of sunflower stalks is found to greatly improve the thickness swelling (TS) value, with acetylated boards showing 19.7% weight gain, meeting the TS requirements of P3 Non-Load-Bearing—Humid and P4 Load Bearing—Dry criteria; however, acetylation adver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 33 publications
0
10
0
Order By: Relevance
“…An alternative means, probably more attractive, is so-called nanotechnology. Nanomaterials have unique characteristics, penetrate effectively and deeply into the wood substrate and improve fundamental properties [18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…An alternative means, probably more attractive, is so-called nanotechnology. Nanomaterials have unique characteristics, penetrate effectively and deeply into the wood substrate and improve fundamental properties [18][19][20][21][22][23][24][25][26][27][28][29][30][31].…”
mentioning
confidence: 99%
“…A great amount of research in this area involves the reaction of anhydrides with wood. Anhydrides react with the hydroxyl groups of the wood cell wall polymers via a nucleophillic reaction pathway [11,12,13]. Researchers have mostly studied the reaction of hydroxyls groups with acetic anhydride, a process that is called acetylation.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…Many studies have examined the sorption of the water vapour of acetylated wood, and the overall stabilisation was well-documented [19,20]. A study by Papadopoulos and Hill investigated the effect that the molecular size of a substituent group may have on the sorption of water vapour, as wood was modified with a series of anhydride molecules of different sizes, which at the same time, produced equivalent levels of cell wall bulking at different levels of hydroxyl substitution [13,21]. The equilibrium moisture content (EMC) data were analyzed by applying the Hailwood–Horrobin sorption model, which enabled the separation of the total sorption into monomolecular and polymolecular sorption.…”
Section: Chemical Modificationmentioning
confidence: 99%
“…Unfortunately, the introduction of acetyl functionalities resulted in a decrease in the internal bond strength. The authors concluded that a mixture of industrial wood chips and sunflower stalks might be appropriate to improve the particleboard specifications [122]. Silphium crops are discussed as promising candidates for biogas production.…”
Section: Cup Plants: Silphium Perfoliatummentioning
confidence: 99%